2016
DOI: 10.4158/ep151108.or
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Agent Orange Exposure Among Thyroid Cancer Patients in the National Va Healthcare System

Abstract: T4 = thyroxine TCDD = 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin TSH = thyroid-stimulating hormone VA = Veterans Affairs VHA = Veterans Health Administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…These proteins with p53 participate to the Nkx2-1/p53/p65/I κ Bα pathway involved in lung carcinogenesis 30 . Here, we show that the same pathway is activated in TCDD-exposed FRTL-5 and in mice, although partially, suggesting a possible mechanism of TCDD-induced thyroid carcinogenesis in human 42 and rodents 43 . Furthermore, the reported results underline that longer exposure times are required to model in vitro the in vivo response to EDCs, as we have previously shown 34 .…”
Section: Discussionmentioning
confidence: 63%
“…These proteins with p53 participate to the Nkx2-1/p53/p65/I κ Bα pathway involved in lung carcinogenesis 30 . Here, we show that the same pathway is activated in TCDD-exposed FRTL-5 and in mice, although partially, suggesting a possible mechanism of TCDD-induced thyroid carcinogenesis in human 42 and rodents 43 . Furthermore, the reported results underline that longer exposure times are required to model in vitro the in vivo response to EDCs, as we have previously shown 34 .…”
Section: Discussionmentioning
confidence: 63%
“…Thyroid disruption has been observed after PCBs or dioxin exposure in the general population, pregnancy and infants . An analysis of the US‐veteran affairs healthcare system showed a higher prevalence thyroid cancer in Vietnam veterans exposed to Agent Orange that was used as defoliant. In another longitudinal study, it was shown that serum TCDD levels were correlated with serum TSH levels .…”
Section: Discussionmentioning
confidence: 99%
“…Populations with low iodine diarrhea are associated with the incidence of follicular and anaplastic carcinomas. 1 Papillary carcinoma is a type of tumor with relatively slow growth. This tumor originates from the follicular cells that produce T4 and Tg in the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…If any sudden onset of pain may be associated with benign lesions of the thyroid such as: thyroid bleeding or acute thyroiditis. 1,14 There are no symptoms that are typical for thyroid cancer, patients generally come with a painless lump in the neck. Anamnesis in patients with thyroid carcinoma most patients come with complaints of a lump on the anterior neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation